Investigation of Abnormal Skin Lesion Analysis System for Melanoma Early Detection Using Image Processing - Sheriff, M.; Dinakaran, K.; Kumaran, M.; Saikiran, B.; Vikram, I. (International Journal of Engineering and Technology, 2018)
In this paper, acquisition of lesion image is carried out and compared using three different segmentation algorithm. Otsuâ€™s method based thresholding technique is used to minimize variance of the background and foreground pixels. Here tone detection and exclusion, three ROI segmentation models (K-means, Fuzzy-C means, Chan Vese model) followed by hybrid feature extraction, and classification methods are carried out. Accuracy, sensitivity, precision , F measure of the acquired lesion image are obtained by using the above segmentation methods and the best method is examined.Â Â